Light stabilizers added to the shell of co-extruded wood/high-density polyethylene composites to improve mechanical and anti-UV ageing properties - Chaozheng Liu; Changtong Mei; Bing Xu; Weimin Chen; Cheng Yong; Ke Wang; Qinglin Wu (Royal Society Open Science, 2018)
Weathering of wood--plastic composites (WPCs) leads to discoloration and cracks, which greatly limits their outdoor application. In this study, light stabilizers (including UV-327, HS-944 and nano-SiO2) were added to the shell of a co-extruded high-density polyethylene-based WPC to improve its anti-ultraviolet (UV) ageing properties and simultaneously to maintain its good mechanical properties. The results showed that UV-327 was the most effective light stabilizer for improving the mechanical and anti-UV ageing properties of the composites among the three stabilizers used. WPC samples combined with 2% UV-327 had the highest retention rates in flexural strength and also had the smoothest surface after 2500 h of UV ageing. The samples with 2% UV-327 added had the best protection for discoloration, showing the lowest values of ΔE* (colour difference) and ΔL* (luminescence) in all samples after 2500 h of UV ageing. WPC samples with 2% UV-327 were also oxidized the least after 2500 h of UV ageing. The results reported herein serve to enhance our understanding of the efficiency of light stabilizers in preventing UV degradation of WPCs, with a view to developing co-extruded WPCs with low cost, high anti-UV ageing properties and good mechanical properties for outdoor applications.